1970
DOI: 10.1042/cs0390115
|View full text |Cite
|
Sign up to set email alerts
|

Iron Metabolism in Patients with Chronic Renal Failure

Abstract: 1. Iron metabolism has been investigated in patients suffering from chronic renal 2. Absorption of labelled inorganic iron was decreased. 3. Radio-iron was lost from the body at a rate comparable to that found in normal 4. The red cell incorporation of radioactive iron was diminished. 5. The results suggest that anaemia in these patients was due to decreased erythropoiesis and not due to iron deficiency despite the evidence of markedly abnormal iron handling presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
1

Year Published

1973
1973
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 5 publications
5
29
0
1
Order By: Relevance
“…The main controversy at present is what is the most effective route to prescribe supplemental iron: oral [14, 15, 16, 17, 18] or parenteral [2, 4, 12, 18, 19, 20, 21, 22, 23]. This derives from conflicting reported observations of intestinal iron absorption in chronic uremic subjects that ranged from unimpaired [24, 25, 26, 27] to substantially reduced [28, 29, 30, 31]. These differences can be explained by the normal large variability in absorption between subjects or in subjects on repeated testing, variable test dosages, use of ferric or ferrous markers, as well as by highly skewed distribution of data [32].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The main controversy at present is what is the most effective route to prescribe supplemental iron: oral [14, 15, 16, 17, 18] or parenteral [2, 4, 12, 18, 19, 20, 21, 22, 23]. This derives from conflicting reported observations of intestinal iron absorption in chronic uremic subjects that ranged from unimpaired [24, 25, 26, 27] to substantially reduced [28, 29, 30, 31]. These differences can be explained by the normal large variability in absorption between subjects or in subjects on repeated testing, variable test dosages, use of ferric or ferrous markers, as well as by highly skewed distribution of data [32].…”
Section: Introductionmentioning
confidence: 62%
“…This number is well beyond the number of cases included in every published study dealing with the problem of intestinal iron absorption in chronic uremics. Besides, the methods applied to evaluate iron absorption in patients affected by chronic renal failure have also been heterogeneous: fecal collection [14], iron red cell utilization [25], whole-body counting [26, 27, 28], the double isotope technique [24], or an oral iron load test [31]. …”
Section: Introductionmentioning
confidence: 99%
“…another study demonstrated that iV and oral iron caused a similar correction in anemia over 6 weeks (17). Several studies have reported that IV iron has greater efficacy with rhuEpo than oral iron, perhaps as a result of reduced iron absorption from the gut and poor patient compliance with oral medication (4)(5)(6)(7)(8)18). although new formulations of iV iron have drastically reduced the risk of immediate adverse effects, a variety of long-term consequences of iV iron have been reported in the literature (15,19).…”
Section: Discussionmentioning
confidence: 99%
“…iV iron bypasses the physiologic controls of iron absorption and storage, thereby exposing the patient to higher levels of circulating free iron and higher tissue levels of iron. a number of authors recently reviewed the link between free or stored iron and a variety of disease states, including cardiovascular disease (18,22), carcinogenesis (19,23) and infection (15,24). the chemical and microbiological quality of water used in dialysate plays a crucial role in the mortality and morbidity of patients on hd.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant iron deficiency, resulting perhaps from a combination of inadequate intake and blood loss (gastrointestinal and during hemodialysis), is often cited as a cause of anemia in patients with chronic renal failure [24, 25, 26, 27, 28]. However, the magnitude or extent of gastrointestinal bleeding in patients with chronic renal failure has not been well quantified [24, 25, 26, 27, 28]. In fact, in several studies the incidence of positive Hemoccult stool tests in asymptomatic patients undergoing dialysis was less than 20% [26, 27, 28].…”
Section: Indicationsmentioning
confidence: 99%